2009
DOI: 10.1002/jso.21463
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management for a malignant bowel obstruction with recurrent gastrointestinal carcinoma

Abstract: Palliative operations for the patients with manifest ascites of MBO are risky and rarely effectively improve oral intake, but this is not considered to be a contraindication for surgical management. Informed consent is therefore important in the surgical management of MBO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Factors such as the presence of ascites and carcinomatosis conveyed a poor prognosis—a finding consistent with previos publications. 22-24 Albumin was shown in our study and by others to be a predictor of survival. 25 Leukocytosis was shown to be a marker of both short-term and overall survival.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Factors such as the presence of ascites and carcinomatosis conveyed a poor prognosis—a finding consistent with previos publications. 22-24 Albumin was shown in our study and by others to be a predictor of survival. 25 Leukocytosis was shown to be a marker of both short-term and overall survival.…”
Section: Resultssupporting
confidence: 77%
“…Other researchers have also shown that the presence of ascites and/or carcinomatosis reduce the likelihood of return to oral in-take. 22 The difficulty with using this outcome in therapy in a retrospective review is the inability to clearly define successful return to oral intake. Given the subjective nature of “tolerating oral intake,” we focused on a more concrete endpoint of mortality on which to base our nomogram.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,14,19,51 Various studies in our review identified ascites as a negative prognostic factor for oral intake and survival after operative and non-operative interventions. 3,4,14,17,40,52 Technical challenges in percutaneous endoscopic gastrostomy (PEG) tube placement can be anticipated in the presence of ascites and diffuse peritoneal metastases involving the greater omentum and gastric serosa. 53,54…”
Section: Resultsmentioning
confidence: 99%
“…Factors known to be associated with diminished surgical benefit include high peritoneal disease burden, multifocal obstruction, ascites, multiple metastatic sites, high-grade histology, poor performance status, and indicators of poor nutrition, such as low serum albumin. 3,4,12,14,33,35,40,41,44,52,68,69 Small bowel obstruction is associated with a poor prognosis, as highlighted in Lodoli et al's study including 98 patients with peritoneal carcinomatosis. Amongst these patients, definitive surgery was not possible in 22% of cases, indicative of technical failure.…”
Section: Block 4 (Agreement: Round I -97% Round Ii -97%)mentioning
confidence: 98%